Content of Foreign Propaganda Directed at Iraq on Facebook: A Case Study of the "Israel in Iraqi Dialect" Page - Awad, Adnan Abd Abdul-Hasan; Dabakh, Widad Ghazi (ALBAHITH ALALAMI, 2025)
Objectives: This research aimed to study and analyze the propaganda content of the Facebook page "Israel in Iraqi Dialect" to understand the propaganda techniques used, the messages directed at the audience, and efforts to promote normalization between Iraq and Israel through the analysis of the media, political, and social discourse presented on the page. Methodology: The researcher used content analysis as the main tool for data collection and interpretation, analyzing the page’s posts using a content analysis form designed for this purpose, within the framework of thematic units. A sample consisting of 20% of the page’s content was selected, relying on a comprehensive census approach to analyze all available content, focusing specifically on the official verified Facebook page managed by the Israeli Ministry of Foreign Affairs. Results: The study found that the page primarily focused on political propaganda content, which constituted 34.50%, aimed at promoting normalization with Iraq. It also showed significant interest in social content, which made up 23.59%, by engaging in direct dialogue with users to promote "social normalization." The most used approach was direct dialogue and speech to enhance audience interaction, indicating the use of sophisticated and targeted propaganda strategies. Conclusion: The research demonstrated that the propaganda content of the "Israel in Iraqi Dialect" page primarily aims to renew dialogue and interaction with the audience through clear and transparent strategies, effectively utilizing social media to serve propaganda goals, particularly in the context of normalization and promoting Israeli interests in the region.